Influência do ruído aeronáutico na população que reside nas imediações da Base Aérea de Santa Maria - Barbosa, Anallu Rosa (2011)
In Brazil, research to quantify annoyance caused by aircraft noise on people living close to airports and air bases is still incipient. Due to the augmented risk of accidents associated to armed aircraft operations but also due to noise emissions by military aircraft air bases, in general, should be located far away from populated areas. Nevertheless, urban development often approximates habited areas to airbases, causing several problems. The actual work aimed to investigate the opinions of a community, composed by civilians and military personnel, that resides close to the Santa Maria airbase (BASM) regarding various aspects, such as aircraft noise and satisfaction with other aspects, such as interference of aircraft noise in daily life, general effects of aircraft noise and individuals attitudes against exposure to aircraft noise. Besides the presence of the BASM and the actual operations on that airbase an expected expansion of the passenger terminal, which is expected to cause an increase in the number of civil aircraft operations and consequently an increase of noise emission, was relevant for the development of this research. The methodology adopted was of qualitative and quantitative nature. By means of observation of the daily life and the use of semistructured interviews the researcher seeked the approximation to the phenomenon of discomfort caused by aircraft noise in the vicinity of Santa Maria Air Base. The qualitative data obtained were analysed using the Grounded Theory, resulting in a conceptual model that shows the relationship between aircraft noise, context of the neighborhood and satisfaction with other aspects than aircraft noise. Based on the results from the qualitative data analysis a structured questionnaire was developed. The questionnaire was applied to 400 individuals in order to measure those aspects that were identified as important during the qualitative approximation the phenomenon of discomfort caused by aircraft noise in the vicinity of Santa Maria Air Base. The results were analysed using univariate and multivariate statistics (Principal Axis Factoring). Factor scores for the effects factor and the annoyance the aircraft operations factor were computed and compared between civilians and military personnel showing both groups are similarly affected by the aircraft operations the comparison of the individual scores of civilians and military personnel on the annoyance the aircraft operations factor showed that the civilians feel more incomfortable than the military personnel